From humanitarian action to development aid in northern Uganda and the formation of a humanitarian-development nexus. Issue 2 (17th February 2017) - Sande Lie, Jon Harald
ABSTRACT: The instituted order of humanitarianism is both changing and challenged. This article addresses the transition between humanitarian action and development aid in northern Uganda, which was driven by the government's ambition to reassert its humanitarian sovereignty by discursively recasting the situation from one of crisis to one of recovery and development, regardless of the persistent humanitarian needs. In response, humanitarian actors either withdrew or moved into development aid. This bourgeoning humanitarian–development nexus questions the nature and future of humanitarianism and whether there is a hierarchy – or contradiction – between the humanitarian mandate and pragmatic approaches to save lives and protect civilians.